al-Wasatiyyah and some of its implications for Islamic built environment - Spahic, Omer (UPM Press, 2015)
This paper discusses the concept of al-wasatiyyah and some of its implications for correctly perceiving the phenomenon of Islamic built environment. The paper concludes that although those implications are rather indirect and implicit in nature, the relationship between the two, i.e., al-wasatiyyah and Islamic built environment, is very strong and reciprocal. Since they have much in common, and since they exert a considerable influence on each other’s ultimate actualization, the concepts of al-wasatiyyah and Islamic built environment should be brought much closer to each other in reviving and unifying the Muslim community. The discussion in the paper focuses on the universality and flexibility of Islamic built environment; how a delicate balance between the form and function in Islamic built environment ought to be established; and avoiding vices which are most often associated with built environment and which are caused by extravagant and excessive tendencies. The nature of the paper is conceptual rather than empirical, featuring a qualitative methodology that combines the descriptive and analytical methods.